Desenvolvimento de modulo de gerenciamento de transdutores para irrigação em agricultura de precisão baseado em internet das coisas - Bastos, Murillo Vinícius Dourado (Universidade Federal do Tocantins, 2021)
The objective of this project is the creation of a micro controlled system for manage ment of transducers on watering for precision agriculture. The system shall send the watering data to a web-based server for processing, making it an internet of things pro ject. Therefore, there will be the junction of two expanding areas, the internet of things and precision agriculture. The development of internet of things based applications is growing because of the integration of television systems, refrigerators, lights, and others with web services. The agriculture is a huge interesting area considering the agriculture of the state of Tocantins characteristics. Because it is an extensive project, this one will bound on the development of a field transducers control system, as well as a review about the technologies for communication and exchange of data with the application server not approached in this project which will handle the user interaction to allow the control of water resources.